Thermo-Responsive Molecularly Imprinted Hydrogels for Selective Adsorption and Controlled Release of Phenol From Aqueous Solution - Si, Zhenhui; Yu, Ping; Dong, Yanying; Lu, Yang; Tan, Zhenjiang; Yu, Xiaopeng; Zhao, Rui; Yan, Yongsheng (Frontiers in Chemistry, 2019)
In this study, Thermo-responsive Molecularly Imprinted Hydrogels (T-MIHs) were developed as a potential effective adsorbent for selectively remove phenol exist in aquatic environments. During the process, N-isopropyl acrylamide (NIPAm) as thermal responsive monomer. The obtained materials were characterized in detail by FT-IR, SEM and TGA. And batch mode adsorption studies were carried out to investigate the specific adsorption equilibrium, kinetics and selective recognition ability of phenol. Reversible recognition and release of template molecule were realized by changing environmental temperatures. Several other phenols were selected as model analytes to evaluate the selective recognition performance of T-MIHs. The T-MIHs have good temperature response, selectivity and reusability, making them possible in applying for phenols separation and controlled release.